Endoscopic ultrasound-guided celiac plexus neurolysis - Soweid, Assaad M (Baishideng Publishing Group Co., Limited, 2010)
Endoscopic celiac plexus neurolysis (CPN) has become the procedure of choice for the management of patients with pancreatic cancer and abdominal pain unresponsive to medical treatment. It is necessary to differentiate between CPN and endoscopic celiac plexus block performed in patients with benign disease. In this review we describe the technique of this procedure with special emphasis on technical details.